Serum Lipidomics Analysis of Classical Swine Fever Virus Infection in Piglets and Emerging Role of Free Fatty Acids in Virus Replication in vitro - Ma, Shengming; Mao, Qian; Chen, Wenxian; Zhao, Mengpo; Wu, Keke; Song, Dan; Li, Xin; Zhu, Erpeng; Fan, Shuangqi; Yi, Lin; Ding, Hongxing; Zhao, Mingqiu; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Lipids metabolism plays a significant role in cellular responses to virus pathogens. However, the impact of lipids metabolism in CSFV infection is not yet confirmed. In the present study, for the fist time, we performed serum lipidomics analysis of piglets infected with CSFV based on ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-QTOF-MS), and identified 167 differentially expressed lipid metabolites. Interestingly, free fatty acids (FFAs) accumulated significantly in these metabolites, accompanied by an increase in sphingolipids and a decrease in glycerolipids and glycerophospholipids, suggesting that CSFV infection markedly changed the serum lipid metabolism of piglets. FFAs are the principal constituents of many complex lipids and are essential substrates for energy metabolism. Based on this, we focused on whether FFAs play a prominent role in CSFV infection. We found that CSFV infection induced FFAs accumulation in vivo and in vitro, which is due to increased fatty acid biosynthesis. Meanwhile, we discovered that alteration of cellular FFAs accumulation by a mixture of FFAs or inhibitors of fatty acid biosynthesis affects progeny virus production in vitro. Furthermore, in the absence of glucose or glutamine, CSFV still has replication capacity, which is significantly reduced with the addition of fatty acid beta oxidation inhibitors, suggesting that the process of FFAs enter the mitochondria for beta oxidation to produce ATP is necessary for virus replication. Finally, we demonstrated CSFV induced FFAs accumulation results in impaired type I IFN signaling-mediated antiviral responses by down-regulating RIG-I-like receptors (RLRs) signaling molecules, which may represent a mechanism of CSFV replication. Taken together, these findings provide the first data on lipid metabolites during CSFV infection and reveal a new view that CSFV infection requires FFAs to enhance viral replication.